Service offshoring: Is Europe different? - Welf Werner (Intereconomics, 2009)
The discussion on the international relocation of jobs in the services sector is not as advanced in Europe as in the USA, where a broad consensus has emerged in recent years that offshoring has very modest effects on the US labour market. One of the key challenges in the European discussion remains the determination of the magnitude and the patterns of offshoring, as the necessary data are often unavailable at the European level. The following article offers a tentative comparison of the effects of offshoring in Europe with those in the USA.
Keywords: 330